Molecular Characterization and Functional Analysis of Krüppel-homolog 1 (Kr-h1) in the Brown Planthopper, Nilaparvata lugens (Stål) - Min-na JIN; Jian XUE; Yun YAO; Xin-da LIN (Journal of Integrative Agriculture, 2014)
The brown planthopper, Nilaparvata lugens (Stål), is the most serious insect pest of rice. It has developed high resistance to traditional insecticides because of their intensive use. Juvenile hormone (JH) analogs have been used successfully to control this species and other pest insects. However, the molecular mechanism of JH signaling is not well understood. Krüppel-homolog 1 (Kr-h1) is a transcription factor involved in the JH pathway. In this study, the Kr-h1 cDNA was cloned and characterized from N. lugens by rapid amplification of cDNA ends (RACE) and reverse transcription PCR (RT-PCR). Its spatial and temporal expression profiles were examined by real-time quantitative PCR, and its function was also studied by RNA interference (RNAi). The open reading frame of NlKr-h1 is 1 833 bp encoding for 611 amino acids. The protein contains eight conserved zinc-finger motifs. NlKr-h1 was expressed at all life stages, with the highest mRNA level in the 4-day embryo. NlKr-h1 mRNA levels rose during each nymphal molt after the 2nd instar. In the adults, the mRNA level in males was significantly higher than that in females of either the macropterous or brachypterous type. The highest expression was observed in the female midgut. NlKr-h1 was activated by juvenile hormone III (JH III) in the 3rd-5th instar nymphs. Disruption of Nlkr-h1 expression by RNAi caused stunted wing development and malformations of both male and female external genitalia. Our findings suggest that Kr-h1 may be a useful target for pest insect management.